2014
DOI: 10.1089/cyber.2014.0173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Brief School-Based Media Literacy Intervention on Digital Media Use in Adolescents: Cluster Randomized Controlled Trial

Abstract: The aim of this study was to evaluate the effects of a four-session school-based media literacy curriculum on adolescent computer gaming and Internet use behavior. The study comprised a cluster randomized controlled trial with three assessments (baseline, posttest, and 12-month follow-up). At baseline, a total of 2,303 sixth and seventh grade adolescents from 27 secondary schools were assessed. Of these, 1,843 (80%) could be reached at all three assessments (Mage=12.0 years; SD=0.83). Students of the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 33 publications
3
95
0
17
Order By: Relevance
“…Six of them (Table 1) described and/or evaluated specific prevention interventions (Busch, de Leeuw, & Schrijvers, 2013; de Leeuw, de Bruijn, de Weert-van Oene, & Schrijvers, 2010; Korkmaz & Kiran-Esen, 2012; Shek, Ma, & Sun, 2011; Turel, Mouttapa, & Donato, 2015; Walther, Hanewinkel, & Morgenstern, 2014). For the purpose of the study, were extracted data relevant to these areas: (a) country in which were data collected, (b) key characteristics of the participants (sample size and segment of the population assessed), (c) intervention characteristic, (d) risk of bias in individual studies, and (e) methodological features (objectives, assessment methods, type of study, and design).…”
Section: Methodsmentioning
confidence: 99%
“…Six of them (Table 1) described and/or evaluated specific prevention interventions (Busch, de Leeuw, & Schrijvers, 2013; de Leeuw, de Bruijn, de Weert-van Oene, & Schrijvers, 2010; Korkmaz & Kiran-Esen, 2012; Shek, Ma, & Sun, 2011; Turel, Mouttapa, & Donato, 2015; Walther, Hanewinkel, & Morgenstern, 2014). For the purpose of the study, were extracted data relevant to these areas: (a) country in which were data collected, (b) key characteristics of the participants (sample size and segment of the population assessed), (c) intervention characteristic, (d) risk of bias in individual studies, and (e) methodological features (objectives, assessment methods, type of study, and design).…”
Section: Methodsmentioning
confidence: 99%
“…Nine out of the 13 studies were conducted in secondary or elementary student populations (combined sample N=9,395). The majority of studies employed pretest-posttest research designs (n=6) and most studies included control groups (n=8), with only one randomized controlled trial (RCT) (Walther et al, 2014). Prevention strategies were predominantly selective (i.e., aimed at a subpopulation at greater risk of developing gaming problems or excessive Internet use) and involved psycho-education.…”
Section: Identification Of Quantitative Studiesmentioning
confidence: 99%
“…In terms of outcomes, four of the six studies reported a successful reduction in problem Internet use symptom scores (Deng et al, 2013;Joo & Park, 2010;Mun & Lee, 2015;Walther et al, 2014), and one study reported no change in symptom levels (Koo, 2013). There were mixed outcomes for school programs in reducing levels of gaming or Internet activity, with one study reporting a reduction in Internet use (Mun & Lee, 2015); another study reporting no change (Yang & Oh, 2007); and one reporting decreased Internet gaming, but no change in Internet use (Walther et al, 2014). Only one study (Montag et al, 2015) employed a universal prevention measure (i.e., wearing a watch to reduce incidental and habitual smartphone use), but this study did not assess an Internet disorder as an outcome variable.…”
Section: Quantitative Prevention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have focused mostly on games and Internet addiction interventions. For example, a cluster randomized controlled trial on the effects of a brief school-based media literacy intervention on computer gaming and Internet use behavior in adolescents indicated that intervention decreased self-reported gaming frequency, gaming time, proportion of excessive gamers, group time, addictive gaming, and Internet addiction 17. Furthermore, a meta-analysis on the treatment of Internet addiction showed no differences between pharmacological and psychological approaches 18.…”
Section: Introductionmentioning
confidence: 99%